Write the equation in standard form:

`y= x^2 - 4x+ 5 ` Use the derivative to find the gradient (multiply the power of x by the coefficient so 2 x 1 = 2 and then minus 1 from the power so `x^2` becomes x and the same for -4x so 1x -4=-4 and the x power reduces to 0 `x^(1-1)` :

`y' = 2x - 4` now substitute the x value in terms of the question(5;10)

= 2(5) - 4

= 6

As a tangent has the equation y=mx + c now substitute the x value, y value and value of m into the new equation to solve for c:

y= mx+c

10= (6)(5) +c

10= 30 + c

-20 = c

`therefore` **y=6x - 20**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now